34 years and counting: the so far experience of World Heritage assets in Thessaloniki, Greece - Zygomalas, Dimitrios (Protection of Cultural Heritage, 2023)
Situated in the north of Greece, Thessaloniki, the country’s second largest city, is foremostly admired for its uninterrupted history of over twenty-three centuries. In solid proof of this remarkable continuity, its historic center is interspersed with a wide array of archaeological and architectural remains that date from Hellenistic to modern times. The most distinguished segment of this unique heritage is by far the city’s Early Christian and Byzantine legacy. More than half of its surrounding walls, fourteen churches and one bath comprise a unique ensemble, revered in the whole of Europe as early as the 19th century. Not surprisingly, at the end of the 20th century, it became one of the first Greek cultural assets to be inscribed on the UNESCO World Heritage List. Thirty-four years have passed since then, a substantial period of time that allows, on the present occasion of the 50th anniversary of the World Heritage Convention, for a review and appraisal of the impact of the inscription. This is precisely the goal of this paper, which will be pursued through an original discussion and evaluation of the consequences of World Heritage status, on one hand for the monuments themselves, and on the other, for their urban, architectural, social and educational setting. Extensive bibliographic research and thorough on-site examination will provide the basis for this discussion, which will culminate with a didactic conclusion as to the degree to which the full potential of the inscription has been achieved or remains to be pursued.